Problematika Penerapan Kontekstualisasi Hadis Tentang Ancaman Orang Yang Meninggalkan Shalat Jum’at Masa Pandemi Covid-19 - Muhammad Alwi HS (Jurnal Studi Hadis Nusantara, 2020)
This article discusses the problems faced in the effort to apply to the contextualization of Hadith about the ‘threat of people who leave the prayer of Friday’, especially in the pandemic Covid-19 in Indonesia. This is based on the fact that state institutions, Indonesian Islamic Community Organizations, and scholars agree on the understanding that the Friday prayers can be left behind during the Covid-19 period. However, the fact in the field shows still very many societies who force to carry out the prayer on Friday. From here, this article shows, at least, four problems seen in the community, ie (1) the emergence of counter-hadith postulate (2) fearing out of the textual understanding of the Hadith, (3) contextualization of the Hadith to the exact application context, and (4) presence of the appreciation of the public to the other religious religion. Therefore, this paper concludes that it is necessary to deliver and the thickement of the contextual understanding of religious values to the public, for the dollains, both based on love and understanding, can be adopted as the context that applies. Contextual understanding of the ‘threat of the threat to the person who leaves the Fray’s prayer’ must be accompanied by the contextual understanding of the religious alleged (Al-Qur’an and Hadith) associated with the sole understanding of the other